Board Diversity and ESG Performance in Indonesia: The Role of Financial Performance Moderators - Setiawan, Bryan; Yusup, Adi Kurniawan (The Indonesian Institute of Science and Technology Research, 2025)
This study investigates the effect of board diversity, specifically gender, age, and nationality, on Environmental, Social, and Governance (ESG) scores in non-financial publicly listed companies in Indonesia from 2019 to 2023. Using Resource Dependence Theory, the study also examines whether profitability and cash flow moderate these relationships. A fixed effects panel regression was applied to 28 firms, resulting in 140 firm-year observations. The results show that gender diversity significantly improves ESG performance, while age diversity has an adverse effect. Nationality diversity alone has no significant impact. Nationality diversity does not substantially influence ESG performance on its own. However, Cash flow and profitability strengthen the effect of ND on ESG. Meanwhile, financial performance indicators alone do not significantly enhance ESG outcomes. These findings suggest that financial capacity allows firms to leverage diverse boards for sustainability goals better. The study offers practical insights for managers and regulators to align board composition with ESG strategies and encourages further research on other forms of board diversity.